Delayed Diagnosis of Volvulus without Complications in Pediatric Patient : A Case Report - Deny Dwi Hartanto; Yasser Maulidan (Universitas Wijaya Kusuma Surabaya, 2024)
Introduction: Volvulus in children is rare occurrence, it’s only about 3-5% cases in worldwide. Without abdominal radiological examination, it is difficult to make diagnosis of volvulus based on history and physical examination alone. The management procedures are also controversial, as some recommend a non-operative approach, while others recommend an operative approach in the form of Ladd's Procedure or laparoscopy. Sigmoidoscopy or a barium enema can be attempted as an initial treatment for sigmoid volvulus. Objective: The purpose of this case report is to discuss why there was a delay in diagnosis of volvulus in this case and how to deal it. It also discusses the approach to diagnosis and management of volvulus in pediatric patients, both at the primary health center and the hospital, and why in this case. Case presentation: In this case, volvulus occurred in a pediatric patient who had sought treatment at a primary health center with a complaint of abdominal pain for nine days without improvement. The complaint was accompanied with constipation and fever. Due to limited facilities in primary health center, the patient was referred to the hospital. Result: At the hospital, after taking the history, performing physical examination, and conducting radiological examination and laboratory tests, the patient was diagnosed with ileus obstruction due to volvulus. Conclusion: Although volvulus is a rare case, volvulus should still be included as a differential diagnosis of abdominal pain in pediatric patients to avoid delayed diagnosis. Delay in diagnosis and management of volvulus can lead to serious complications and even life-threatening conditions